Serum iron and total iron binding capacity in severely malnourished children - Md. Atiar Rahman; M. A. Mannan; Md. Hamidur Rahman (Bangladesh Pharmacological Society, 2007)
Serum iron, total iron binding capacity and plasma protein of severely malnourished children of 12-59 months of age were compared with that of normal healthy children. Mean serum total protein and albumin level in normal children were 76.33 ± 0.51, 43.50 ± 0.38 gm/L respectively which was significantly higher (p<0.05) than that of malnourished children (64.39 ± 0.57, 30.17 ± 0.45 gm/L). But mean serum globulin level was (34.22 ± 0.27 gm/l) higher in malnourished children than that of normal children (32.83 ± 0.53 gm/L). The mean serum iron and transferrin saturation level were (78.72 ± 11.12 µg/dL, 23.38 ± 1.97%) significantly high (p<0.001) in severely malnourished children than in normal children, whereas serum TIBC had no significant difference between these two groups.